Development of facial palsy during immunoadsorption plasmapheresis in Miller Fisher syndrome: a clinical report of two cases. Issue 3 (1st March 1998) - Chida, Keiji; Takase, Sadao; Itoyama, Yasuto
Abstract : Immunoadsorption plasmapheresis (IAP) using a tryptophan linked gel column has been shown to effectively remove serum IgG anti-GQ1b antibody which may contribute to the pathogenesis of Miller Fisher syndrome. Two patients are reported on with Miller Fisher syndrome, who developed bilateral facial palsy during IAP using a tryptophan column, while ophthalmoplegia, ataxia, and, areflexia were improving. In these patients, the titre of anti-GQ1b antibodies was reduced. The IAP using a tryptophan column has a beneficial effect on Miller Fisher syndrome but may not inhibit the development of facial palsy. The mechanism of such a dissociated effect of IAP on Miller Fisher syndrome is discussed.